1998
DOI: 10.1016/s0895-7061(98)00137-x
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory 24-h blood pressure monitoring in healthy, middle-aged smokeless tobacco users, smokers, and nontobacco users☆

Abstract: Ambulatory 24-h blood pressure monitoring was conducted in 135 healthy, normotensive, middle-aged (35 to 60 years) men, with no antihypertensive medication, to study the influence of habitual smokeless tobacco use (n = 47) and smoking (n = 29) on diurnal blood pressure and heart rate. Comparisons were made with nonusers of tobacco (n = 59). Adjustments were made for differences in age, body mass index, waist-hip ratio, physical fitness, and alcohol intake. Daytime ambulatory heart rates were significantly (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
71
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 29 publications
13
71
0
2
Order By: Relevance
“…The results showing that the mean daytime systolic and diastolic blood pressure measurements were significantly higher in smokers regardless of whether or not they used antihypertensive medication agree with the majority of studies conducted in other countries with normotensive [17][18][19] and hypertensive patients [20][21][22][23] .…”
Section: Discussionsupporting
confidence: 86%
“…The results showing that the mean daytime systolic and diastolic blood pressure measurements were significantly higher in smokers regardless of whether or not they used antihypertensive medication agree with the majority of studies conducted in other countries with normotensive [17][18][19] and hypertensive patients [20][21][22][23] .…”
Section: Discussionsupporting
confidence: 86%
“…This is in accordance with results from a study by Dyer et al (1982), which showed a stronger association between smoking and pure systolic hypertension. However, numerous epidemiological studies have shown that blood pressure is lower in smokers than non-smokers (Karvonen et al 1959;Higgins and Kjelsberg 1967;Seltzer 1974;Berglund and Wilhelmsen 1975;Goldbourt and Medalie 1977;Gofin et al 1982;Agner 1983;Savdie et al 1984;Green et al 1986;Rosengren and Wilhelmsen 1987;Green et al 1991;Imamura et al 1996;Okubo et al 2002;Nagahama et al 2004;Okubo et al 2004;Wang et al 2006), although several other reports have found that smoking raises blood pressure (Elliott and Simpson 1980;Dyer et al 1982;Bolinder and de Faire 1998). Moreover, other studies have speculated about the effects of smoking on blood pressure on the basis of changes in blood pressure that were observed after smoking cessation, and one of these studies reported that blood pressure rose after smoking cessation (Wilhelmsen et al 1986), while others reported that smoking cessation had no clear-cut effect on blood pressure level (Schoenenberger 1982;Puddey et al 1985;Tuomilehto et al 1986;Green and Harari 1995) .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, numerous reports have found that smoking reduces blood pressure (Higgins and Kjelsberg 1967;Seltzer 1974;Berglund and Wilhelmsen 1975;Goldbourt and Medalie 1977;Gofin et al 1982;Agner 1983;Savdie et al 1984;Green et al 1986;Rosengren and Wilhelmsen 1987;Green et al 1991;Imamura et al 1996;Okubo et al 2002;Nagahama et al 2004;Okubo et al 2004;Wang et al 2006). In contrast, several other reports have found that smoking raises blood pressure (Elliott and Simpson 1980;Dyer et al 1982;Bolinder and de Faire 1998), while still others failed to confirm any effect on blood pressure (Arkwright et al 1982;Criqui et al 1982;Lang et al 1983;Simons et al 1984). Few large epidemiological studies on the effects of smoking on blood pressure have considered the confounding effects of such factors as age, obesity, blood chemistry, lifestyle or working conditions.…”
mentioning
confidence: 99%
“…Some studies have shown that the use of oral snuff or smokeless tobacco may predispose a person to higher systolic and diastolic blood pressures, 5,6,7 and significantly increase the risk for myocardial infarction. 8 A few studies have also suggested an acute elevation of blood pressure following snuff-dipping, ascribed to the mineralocorticoid activities of nicotine, the high sodium content and possibly the effect of liquorice additives.…”
Section: Introductionmentioning
confidence: 99%
“…3 Most of the existing studies on the association of snuff with cardiovascular disease are derived mainly from the study of Caucasian male snuff-dippers in developed countries. 5,9,10,11,12,13 Due to the lack of consistent associations between snuff and major diseases (particularly in developed nations), snuff is promoted as a reduced-harm product. 15,16 Although snuff use in South Africa, which includes the nasal use of both moist and dry snuff, may be different from the pattern of use in developed nations, 17,18 it is similarly perceived by some South African adolescents as a safer alternative to cigarettes.…”
Section: Introductionmentioning
confidence: 99%